Mammary epithelial cell transformation is associated with deregulation of the vitamin D pathway - Kemmis, Carly M. (2008)
The vitamin D endocrine system mediates anti-proliferative and pro-differentiating signaling in multiple epithelial tissues, including mammary gland and breast tumors. The vitamin D metabolite 1α,25(OH)(2)D(3) mediates growth inhibitory signaling via activation of the vitamin D receptor (VDR), a ligand dependent transcription factor. 1α,25(OH)(2)D(3) is synthesized from 25(OH)D(3) (the major circulating form of the vitamin) by the mitochondrial enzyme CYP27b1 in renal and other tissues. Human mammary epithelial (HME) cells express VDR and CYP27b1 and undergo growth inhibition when exposed to physiological concentrations of 25(OH)D(3), suggesting that autocrine or paracrine vitamin D signaling contributes to maintenance of differentiation and quiescence in the mammary epithelium. In the current studies we tested the hypothesis that cancer cells would exhibit reduced sensitivity to vitamin D mediated negative growth regulation. We used a series of progressively transformed HME cell lines expressing known oncogenic manipulations to study the effects of transformation per se on the vitamin D pathway. We report that mRNA and protein levels of VDR and CYP27b1 were reduced greater than 70% upon stable introduction of known oncogenes (SV40 T antigens and H-rasV12) into HME cells. Oncogenic transformation was also associated with reduced 1α,25(OH)(2)D(3) synthesis, and cellular sensitivity to growth inhibition by 1α,25(OH)(2)D(3) and 25(OH)D(3) was decreased approximately 100-fold in transformed cells. These studies provide evidence that disruption of the vitamin D signaling pathway occurs early in the cancer development process.